[Cal Poly Glee Club with bus] (1938)
The Varsity Glee Club posing for a portrait in front of their bus in front of Crandall Gym. They are dressed semi-formally in white sweaters with the Cal Poly insignia stitched on the lower corner of their sweaters. In the picture, front row, from the left, Robert Brown, T. Niiro, R. Kobayashi, L. Kolding, Secretary-Treasurer L. Frame, President G. Milne, P. Giampaoli, Manager E. Ford, J. Pappas, E. Beers. Second row, G. Sondeno, H. Comstock, Director H. P. David?son, F. Spessard, M. Sondeno, F. Brown, A. Parks, A. Tognetti, C. Cash, H. Barham, E. Russell, R. Hall, H. Petree, W. Goold, K. Carter, J. Harter, R. Lindesmith, H. Turton, R. Owens, J. O'Brien, M. Williams, R. Morrison, A. Nitta, H. Boltz, E. Hubbell, H. Wallace, Reg Brown. Absent, A. Solesbee, J . Cohen. The photo was printed in the 1938 El Rodeo yearbook.